2016
DOI: 10.1097/icu.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography platforms and parameters for glaucoma diagnosis and progression

Abstract: OCT technology is advancing not only as a tool for structural assessment, but also as a multimodality tool to assess both structure and function to enhance our understanding of glaucoma, and ultimately clinical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
(23 reference statements)
0
23
0
Order By: Relevance
“…The persistence of axonal swelling, which most probably relates to a stasis of organellar transport, resolves at a slower rate. Lacking a longitudinal follow‐up at the crucial transition from pre‐clinical to conversion, we can only speculate on what triggers conversion and we cannot exclude that the VD reduction is only a consequence of optic nerve atrophy, similarly to other chronic optic neuropathy . However, one hypothesis to explain the catastrophic rapidity of disease onset, which occurs in days to weeks may implicate some anatomical considerations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The persistence of axonal swelling, which most probably relates to a stasis of organellar transport, resolves at a slower rate. Lacking a longitudinal follow‐up at the crucial transition from pre‐clinical to conversion, we can only speculate on what triggers conversion and we cannot exclude that the VD reduction is only a consequence of optic nerve atrophy, similarly to other chronic optic neuropathy . However, one hypothesis to explain the catastrophic rapidity of disease onset, which occurs in days to weeks may implicate some anatomical considerations.…”
Section: Discussionmentioning
confidence: 95%
“…Using the split‐spectrum amplitude‐decorrelation angiography (SSADA) algorithm, vascular perfusion can be quantified . OCT‐A has been used to detect microvasculature reduction in other optic neuropathies . To date, only single case reports have qualitatively described microvascular changes in LHON detected by OCT‐A …”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that observed pre-perimetric structural losses could be an artifact of the testing method. SAP only has the ability to detect functional deficits after at least 25–50% of RGCs have undergone apoptosis (Harwerth et al, 1999; Kerrigan-Baumrind et al, 2000; Medeiros et al, 2013; Miglior et al, 2005; Mwanza and Budenz, 2015; Quigley et al, 1989; Strouthidis et al, 2006; Wollstein et al, 2005). Harwerth et al, for example, demonstrated in a population of 10 rhesus monkeys that SAP testing could not provide a useful estimate of ganglion cell losses at early stages of VF defects.…”
Section: The Expanding Role Of Ao-octmentioning
confidence: 99%
“…Doppler OCT, although able to detect to motion parallel to the OCT beam, has a limited ability to visualize motion predominantly perpendicular to the probe, such as is the case in retinal and choroidal circulations. Although hemodynamic parameters may be useful in diagnosis 78 and management of glaucoma, its true clinical utility remains to be determined.…”
mentioning
confidence: 99%